CONSEQUENCES OF PRENATAL AND POSTNATAL EXPOSURE TO PASSIVE SMOKING ON CHILDREN - Voichița Hurgoiu (Amaltea Medical Publishing House, 2008)
Passive tobacco smoking is responsible for the prenatal and postnatal negative health effects on children. The consequences of maternal smoking during pregnancy included: placenta alterations, intrauterine growth retardations, low birth weight, perturbation in lung, brain and parathyroid gland functions, sudden infant death syndrome, immune alterations, susceptibility to respiratory diseases, perturbations of growth, cognitive development and behavioral disorders in infancy and childhood. Postnatal smoke exposure favours the alergic and infectious lung diseases: wheezing, cough, alergic rhinitis, wheezy bronchitis to onset asthma. The passive smoking favours earlier instalation of the tabagisme by adult imitation or nicotine dependence.